A prática coral juvenil transitando em ambientes formais e não formais: perspectivas aplicadas à educação musical - Daroz, Irandi Fernando [UNESP] (2014)
Among the collective artistic practices, music plays an important role because it is present among youth in autobiographical terms constituting a powerful communication tool. This study stems from the need to understand youth cultures and their modes of representation, especially in regard to music listening, so this concern may indicate more attractive forms of the choral singing practice with young people. We stress the importance of this activity as a mean to retrieve human values in what regards the sensibility, subjectivity and affectivity in contrast to the current problems faced by society such as the alienation promoted by media and the cultural industry, which often emphasize what is superficial and the fleeting rather than the deeper and permanent relations of music as a active leisure able to promote relevant ethic-aesthetic experiences, start creative processes and stimulating aspects of fruition. Therefore, we refer to the everyday Sociosophy unveiled in the theories of José Machado Pais, Michel Maffesoli, Giles Deleuze, Félix Guattari e Mihaly Csikszentmihalyi. We also highlight the youth choir practice as an effective and accessible tool to music education from the perspective of understanding how to include this activity in the school environment. We consider the importance of centralizing the learning process in the student/singer's musical knowledge in order to outline strategies for intervention that can expand these references by a process of re-signification of the musical memory, promoting a dialogue between the scholarly and popular cultures. In this perspective it was essential to characterize the work of the choir conductor both in formal settings (in school), non-formal or informal (outside of school) to identify characteristics and professional behaviors adjusted to the Brazilian reality, noting that, in most cases, the choir is the only possible access to music literacy